PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN KONTEKSTUAL - Zulyadaini Zulyadaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Learning with the contextual approach (Contextual Teaching and Learning, CTL) is an approach to learning that begins with taking, simulate, tells the story, dialogue, ask and answer or discussion on Genesis of the real world of everyday life experienced by students, then lifted into the concept that will be studied and discussed. Throughthis approach, allowing the occurrence process of learning in which the student's academic abilities and understanding of mengeksplorasikan in a variety of contexts, inside or outside the classroom, to be able to resolve the problems facing either independently or in a group. Contextual learning means making a connection to find meaning, do the work, encourage students to always on, set the self-study, working together in groups, emphasizes creative thinking and critical management, on an individual basis, reaching high standards and using authentic assessment. Student involvement in the learning process of this among others is; a) perform observation, b) do exploration, c) do inkuiri, d) make hypotheses, conjectures, making e) f) make generalizations, and g) apply. Contextual learning can create meaningfulness learning experience and improve academic performance of students. Contextual learning practically also promised an increase in interest, interest in learning of students from different backgrounds as well as increasing participation by encouraging students to actively in providing the opportunity to them to connect and apply the knowledge they have gained.Key words: konstekstual, real world Approach, student involvement